2023
DOI: 10.1186/s12891-023-06171-w
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of massive bone defects after femoral tumor resection using two new-designed 3D-printed intercalary prostheses: a clinical analytic study with the cooperative utilization of multiple technologies

Abstract: Background To reconstruct massive bone defects of the femoral diaphysis and proximal end with limited bilateral cortical bone after joint-preserving musculoskeletal tumor resections, two novel 3D-printed customized intercalary femoral prostheses were applied. Methods A series of nine patients with malignancies who received these novel 3D-printed prostheses were retrospectively studied between July 2018 and November 2021. The proximal and diaphyseal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…This review article discusses the tremendous progress being made with potential future applications in the field of bioengineering [3]. In this study, the authors report on their progress made with new developments in endoprosthetic replacement using a new design and material [13]. …”
Section: Read This Nextmentioning
confidence: 99%
See 2 more Smart Citations
“…This review article discusses the tremendous progress being made with potential future applications in the field of bioengineering [3]. In this study, the authors report on their progress made with new developments in endoprosthetic replacement using a new design and material [13]. …”
Section: Read This Nextmentioning
confidence: 99%
“…c In this study, the authors report on their progress made with new developments in endoprosthetic replacement using a new design and material [13].…”
Section: Read This Nextmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, three-dimensional-printed (3DP) endoprosthesis has become a powerful tool for complex reconstruction in extremities, improving limb and joint salvage rates [ 15 ]. Moreover, a 3DP short stem with porous structure seems to be an alternative for short-segment fixation and has been reported that creates a stable endoprosthesis fixation in intercalary reconstruction [ 16 18 ]. However, the clinical efficacy and outcomes of using this technique in osteoarticular reconstruction for fixation of the massive endoprosthesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%